Mahmud Kashgari's Work "Devonu Lug'otit Turk" is an Important Scientific Heritage (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Mahmud Kashgari's work "Devonu lug'otit turk" stands out among the works created in the history of the Uzbek language due to its scientific value. The scientist worked on this work for many years, traveled around the country and collected material for many years, traveled one by one to the vast and large territory inhabited by the Turks, determined the lifestyles, customs, professions, residences, and influence of the clans, tribes, peoples. and carefully studied the peculiarities of their languages.